The Influence of Social Media and Digital Communication on Language Use and Evolution - Dr. Hirenkumar P. Chaudhary; Dr. Japeshwari Asarsa (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In today’s digital age, social media has revolutionized the way we communicate and interact with one another. This article Explores the fascinating connection between social media and the evolution of language. As more the people engage in online conversations, the impact of social media on our language becomes increasingly evident. From the use of emojis to the creation of new words and abbreviations, social media platforms have significantly influenced how we express ourselves. Today we delve into the various ways in which social media has shaped the evolution of language and explore its implications for communication in the modern world.